2017
DOI: 10.15453/2168-6408.1278
|View full text |Cite
|
Sign up to set email alerts
|

Generation Y Health Professional Students’ Preferred Teaching and Learning Approaches: A Systematic Review

Abstract: Generation Y or Millennials are descriptors for those born between 1982 and 2000. This cohort has grown up in the digital age and is purported to have different learning preferences from previous generations. Students are important stakeholders in identifying their preferred teaching and learning approaches in health professional programs. This study aimed to identify, appraise, and synthesize the best available evidence regarding the teaching and learning preferences of Generation Y health professional studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 23 publications
0
40
0
Order By: Relevance
“…This demonstrates how undergraduate training has shifted from lecture-style methods to exploring e-learning based methods to better suit modern learning styles. 10,11 For interns who have not been exposed to e-learning or video tutorials previously, watching videos from the Internet or social media is ubiquitous nowadays and success is achieved with little effort, even by the previously uninitiated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrates how undergraduate training has shifted from lecture-style methods to exploring e-learning based methods to better suit modern learning styles. 10,11 For interns who have not been exposed to e-learning or video tutorials previously, watching videos from the Internet or social media is ubiquitous nowadays and success is achieved with little effort, even by the previously uninitiated.…”
Section: Discussionmentioning
confidence: 99%
“…9 Millennials tend to have increased accessibility to the Internet, a predisposition to gaming, excessive attachment to their mobile phones and are comfortable with social networking using technology. 10 These younger generations tend to be taught by the older generation (traditional and baby-boomer generations), which Gillipsie termed, the 'generational gap' . 11 This generational gap may be a barrier to effective teaching and training.…”
Section: Introductionmentioning
confidence: 99%
“…With experiential learning, group projects and individual assignments occur in parallel with practical experience with organizations or clients. Instructional strategies for the development of professional reasoning are designed to guide students in applying practical experiences to didactic content (Hills & Levett-Jones, 2017;Knecht-Sabres & Kovic, 2013). Hills and Levett-Jones (2017) conducted a systematic review on the preferred learning methods of health professions students.…”
Section: Experiential Learningmentioning
confidence: 99%
“…Instructional strategies for the development of professional reasoning are designed to guide students in applying practical experiences to didactic content (Hills & Levett-Jones, 2017;Knecht-Sabres & Kovic, 2013). Hills and Levett-Jones (2017) conducted a systematic review on the preferred learning methods of health professions students. They reported that 85% of recent health professions students preferred hands-on learning and actual practice versus any other instructional method related to learning clinical skills.…”
Section: Experiential Learningmentioning
confidence: 99%
“…Health professional education programs are currently still primarily comprised of contentfocused lectures (Hills et al, 2017), which students often regard as disengaging (Toothaker & Taliaferro, 2017). Toothaker and Taliaferro (2017) found that during a course lecture, many nursing students partake in activities unrelated to the lecture, such as completing assignments from other courses or surfing social media.…”
mentioning
confidence: 99%